Examination of cross-reactivity among Trypanosoma evansi, Theileria annulata and Babesia bigemina by Te-mAB-LAT and PCR - Reema, Reema; Chaudhri, S S; Singh, A (The Indian Journal of Animal Sciences, 2012)
Blood and serum samples from 55 crossbred cows detected positive for haemoprotozoan infections (T. evansi-11, T. annulata- 23 and B. bigemina- 21) on examination of stained blood smears were collected and stored for T. evansi antigen detection monoclonal antibody- based latex agglutination test (Te-mAb-LAT) and polymerase chain reaction (PCR). Trypanosoma evansi mAb-LAT revealed circulating antigens in serum samples of 18 animals, including 11 confirmed positive for T. evansi, 3 confirmed positive for T. annulata and 4 confirmed positive for B. bigemina. The DNA fragments of the size 227 bp, 175 bp and 721 bp were amplified by PCR assays using specific primers for evansi, B. bigemina and T. annulata, respectively. The animals confirmed positive by stained smear examination for specific haemoprotozoa (T. evansi/ B. bigemina/ T. annulata) were also positive with specific PCR assay (T. evansi, Te- PCR/ B. bigemina, Bb-PCR/ T. annulata, Ta-PCR). The Te-PCR was observed free from any cross-reactivity with annulata/ B. bigemina whereas Ta-PCR revealed 5 of 21 B. bigemina infected samples positive for T. annulata and Bb-PCR detected 1 out of 11 T.evansi infected samples and 12 of 23 T. annulata infected samples positive for bigemina. It indicated that some of the animals had mixed infections of T. annulata and B. bigemina which is a common occurrence due to mixed infection of their vectors feeding on animals. Secondly, it was possible to have missed detection of low level of infection on microscopic examination of the stained blood smears.The detection of circulating antigens in 7 blood samples (3 of T. annulata and 4 of B. bigemina infected animals) with Te-mAb-LAT, without their detection by Te-PCR was possibly due to previous exposure of these animals with evansi and subsequent treatment with trypanocidal drug. It is inferred that Te-mAb-LAT, being simple to perform, rapid, convenient and cost-effective could be quite suitable for diagnosis of trypanosomosis at field level and PCR being sensitive and specific has its utility at the laboratory level.